Odpowiedzi

2009-12-17T23:24:45+01:00
A) y= 2x² + 4x -2
a=2
b=4
c=-2
Δ=16-4*2*(-2)=16+16=32
√Δ=4√2

x₁=(-4-4√2)/4=-1-√2
x₂=(-4+4√2)/4=-1+√2

y=a(x-x₁)(x-x₂)
y=2(x+1+√2)(x+1-√2)

b) y= -5x²- 2x-1
a=-5
b=-2
c=-1
Δ=4-4*(-5)*(-1)<0
brak miejsc zerowych-brak postaci iloczynowej

c) y= 6x²- 2x -1
a=6
b=-2
c=-1
Δ=4-4*6*(-1)=4+24=28=4*7
√Δ=2√7
x₁=(2-2√7)/12=(1-√7)/6
x₂=(2+2√7)/12=(1+√7)/6

y=a(x-x₁)(x-x₂)
y=6(x- (1-√7)/6)(x- (1+√7)/6)

d) y= 3x²+2x-1
a=3
b=2
c=-1
Δ=4-4*3*(-1)=4+12=16
√Δ=4

x₁=(-2-4)/6=-6/6=-1
x₂=(-2+4)/6=2/6=1/3

y=a(x-x₁)(x-x₂)
y=3(x+1)(x- 1/3)